2018
DOI: 10.1039/c8gc01764f
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free sulfenylation of indoles with sulfinic esters in ethanol

Abstract: A novel catalyst-free method for the synthesis of structurally diverse indole thioethers in moderate to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 75 publications
0
19
0
1
Order By: Relevance
“…To identify the best reaction conditions, ethyl 4methylbenzenesulfinate (1a) and 2-phenylimidazo[1,2a]pyridine (2a) were initially used as the model substrates (Table 2). Literature method of catalyst free sulfenylation of indoles in ethanol using sulfinic esters 17 was unsuccessful in our case, and the utilization of hydrazine hydrate 18 as reducing agent could not improve the situation (Table 2, entries 1-2). Further literature survey revealed that anhydrides are efficient reagents 19 for the deoxygenation of arylsulfoxides to the corresponding sulfides.…”
Section: Iodine-mediated Sulfenylation Of Imidazo[12-a]pyridines Witmentioning
confidence: 81%
“…To identify the best reaction conditions, ethyl 4methylbenzenesulfinate (1a) and 2-phenylimidazo[1,2a]pyridine (2a) were initially used as the model substrates (Table 2). Literature method of catalyst free sulfenylation of indoles in ethanol using sulfinic esters 17 was unsuccessful in our case, and the utilization of hydrazine hydrate 18 as reducing agent could not improve the situation (Table 2, entries 1-2). Further literature survey revealed that anhydrides are efficient reagents 19 for the deoxygenation of arylsulfoxides to the corresponding sulfides.…”
Section: Iodine-mediated Sulfenylation Of Imidazo[12-a]pyridines Witmentioning
confidence: 81%
“…A similar disproportionate reaction of sodium benzenesulfinate to a thiosulfonate has just been observed by Wang et al 86 Then, this intermediate 8a as an electrophile reacted with 1a to form the desired product 3a . 87 , 88 Subsequently, the benzenesulfinic acid generated can be converted into 8a in the presence of TBAI. 89 , 90 Finally, a sulfenylation cycle was established.…”
Section: Resultsmentioning
confidence: 99%
“…3‐(phenylthio)‐1H‐indole (3 mb) : R f =0.35 (5% ethyl acetate/hexane); off white solid; mp 155–157 °C; yield 41% (54 mg); 1 H NMR (400 MHz, CDCl 3 ) δ 8.42 (s, 1H), 7.62 (d, J =8.0 Hz, 1H), 7.49 (d, J =2.0 Hz, 1H), 7.45 (d, J =8.0 Hz, 1H), 7.30–7.26 (m, 1H), 7.20–7.14 (m, 3H), 7.13–7.09 (m, 2H), 7.05 (t, J =7.2 Hz, 1H); 13 C NMR (100 MHz, CDCl 3 ) δ 139.4, 136.6, 130.8, 129.3, 128.8, 126.0, 124.9, 123.2, 121.0, 119.8, 111.7, 103.0.…”
Section: Methodsmentioning
confidence: 99%